Applying the self‐determination theory continuum to unhealthy eating: Consequences on well‐being and behavioral frequency. Issue 7 (11th April 2020) - Kadhim, Nada; Amiot, Catherine E.; Louis, Winnifred R.
Abstract: The present research applies self‐determination theory (SDT) to the context of unhealthy eating. The extent to which each of the six types of motivations stemming from the SDT continuum applies to unhealthy eating is examined, as well as the contribution of each motivation for eating unhealthily in predicting psychological well‐being and frequency of unhealthy eating. A three‐wave longitudinal study ( N  = 379) was conducted before, during, and after the Christmas holidays. Results demonstrated that three types of motivations (i.e., identified, introjected, and external regulation) for unhealthy eating fluctuated over time and peaked during the holidays, a time when unhealthy eating becomes especially salient in Western societies. However, amotivation for unhealthy eating reached its lowest level during the holidays. While identified regulation was associated with greater well‐being, introjected regulation, and amotivation for unhealthy eating were linked with lower well‐being. Integrated regulation was associated with lower well‐being only before and after the holiday period. Finally, the integrated, introjected, external regulations, and amotivation were linked to higher frequency of unhealthy eating. These results confirm that each type of motivation presents distinct patterns of associations with well‐being and actual behavior. Results also demonstrate that the social context in which eating takes place can have an impact on the relationship between motivations and well‐being as well as behavior.